The role of kynurenine pathway and kynurenic aminotransferase alleles in postpartum depression following cesarean section in Chinese women. Issue 4 (26th February 2020) - Quan, Chengxuan; Wang, Saiying; Duan, Kaiming; Ma, Jiahui; Yu, Heya; Yang, Mi; Hu, Na; Long, Ge; Zeng, Guang; Huang, Zhendong
Abstract: Objectives: A growing body of data indicates that the kynurenine pathway may play a role in the pathogenesis of postpartum depressive symptoms (PDS). Kynurenic aminotransferase (KAT) is an important kynurenine pathway enzyme, catalyzing kynurenine (KYN) into kynurenic acid (KYNA). This study investigated as to whether genetic variations in KAT are associated with PDS. Methods: A cohort of 360 Chinese women scheduled to undergo cesarean delivery was enrolled into this study. PDS was determined by an Edinburgh Postnatal Depression Scale (EPDS) score ≥ 13. A total of eight KAT single nucleotide polymorphisms (SNPs) were genotyped and their association with PDS investigated. Serum concentrations of KYN, KYNA, and quinolinic acid (QUIN) in women with or without PDS were also measured. This allowed the determination of the KYNA/KYN ratio, which is reflective of KAT activity. Results: Postpartum depressive symptoms incidence was 7.2%. Advanced maternal age, lower education, antenatal depression, and postpartum blues were risk factors for PDS ( p  < .05). Women with PDS, versus non‐PDS, had heightened KYN levels one day prior to surgery (ante‐d1) ( p  < .05), as well as having significantly lower KYNA and higher QUIN levels at postnatal day three (post‐d3) ( p  < .05). Women with, versus without, PDS also had a significantly higher QUIN/KYNA ratio at post‐d3 ( p  < .05). KAT activity was significantly lower in women with, versus without, PDS at ante‐d3 ( p  < .05). No significant association was evident between the KAT SNPs and PDS. Conclusion: Our data support a role for alterations in the kynurenine pathway in the pathogenesis of PDS, although no significant association was found for the eight tested KAT SNPs with PDS. Abstract : Our data support a role for alterations in the kynurenine pathway in the pathogenesis of PDS, although no significant association was found for the eight tested KAT SNPs and PDS.